A field study of the role of nurses in advocating for safe practice in hospitals. (19th November 2013) - Choi, Sandy Pin‐pin; Cheung, Kin; Pang, Samantha Mei‐che
Abstract Aim To explicate nurses' role and the underlying processes involved in advocating for safe practice in hospitals. Background Nurses' role as patient advocates in safeguarding patients' interests and well‐being is constantly upheld. As previous studies have fallen short in delineating the processes of how and in what conditions the patient advocate role is operationalized, this study was conducted to fill the evidence gap through examining nurses' advocacy role and practices in real clinical contexts. Design A field study approach that involved multiple methods of data collection was adopted. Methods This study was conducted from February 2010–March 2011 in four medical units in two public hospitals in Hong Kong. Empirical data were generated from weekly field observations, review of relevant documents and individual semi‐structured interviews with 28 nurses and were then analysed through a comparative analysis process. Results Nurses play an integral role in ensuring safe practice in hospitals through mitigating risk arising from sudden changes in patients' health conditions and the hospitalization process and correcting near‐misses for co‐workers to prevent harm. The modelling of expert nurses and team‐based learning emerged as essential factors facilitating the development of nurses' advocacy role and practices. The state of 'limited advocacy', as characterized by the adoption of disempowering and coercive measures to ensure patient safety, clearly indicates a need to re‐examine the concept of advocacy in contemporary health care. Conclusion The findings contribute to a more complete understanding of nurses' advocacy role and practices, which have a significant bearing on patient safety.